Investigating the role of Entropy in Design Evaluation Process: A Case Study on Municipality Buildings - GÜZELCİ, ORKAN ZEYNEL (My University, 2017)
The concept of entropy, which can be used to measure physical disorder, has been rediscovered by Shannon to measure the irregularity in information. Entropy measurements are made by considering one or more factors. Specific features such as color, shape, element type, height, material related with architectural compositions can be considered as factors and the amount of information carried by the building depending on one or more of these factors can be measured. In this study, it is questioned whether there is a relationship between entropy values of municipal building competition projects, which are measured in relation to the factors, and the building is considered successful by the competition jury. In order to conduct this examination, the entropy values of the projects, which respected to the same architectural program and won various awards in the project competitions were calculated. Before making comparisons, measurements were made according to solid-void ratios on the plan layout, the shapes of closed and discrete spaces, and the distribution of functions. A discussion was made on the usability of entropy method in the design phase, which gave solid and precise results according to the results of the comparisons.
Keywords: Entropy; Architectural Competition; Municipality Buildings